The Relationship Between Financial Leverage and ESG Disclosure on Greenwashing - Noor, Maraditta; Sari, Martdian (Business Management Journal, 2026)
Greenwashing has become a critical issue, as companies may project an environmentally responsible image through reports without reflecting it in real practices. This study examines how financial (leverage) and nonfinancial ( ESG disclosure) pressures influence such behavior. This study uses data obtained from the financial and sustainability reports of energy sector companies listed on the Indonesia Stock Exchange for the period 2021- 2023, then processed with linear regression analysis using SPSS version 27. The results showed that companies with high financial leverage tend to avoid greenwashing. This means that financial discipline and compliance can arise from creditor pressure. In contrast, ESG disclosure encourages greenwashing practices, which suggests that companies tend to use sustainability reporting as a symbolic means to maintain their legitimacy and image in front of the public. These findings provide new insights for agency and legitimacy theories, as well as important input for regulators and companies, so that the concept of sustainability is not just for image and formality.